SURFACTANT PROPERTIES EVALUATION FOR CHEMICAL FLOODING - Sugihardjo Sugihardjo (Testing Center for Oil and Gas LEMIGAS, 2008)
The need of EOR techniques in the late field production period is essential to get the third wind of incremental oil. Chemical injections are proven technologies not only at the laboratory scale but also at the field scale which have been implemented in many parts of the world. Surfactant is an important chemical in this technology, which mostly has been used to reduce the capillary trap of the oil in the reservoirs. The selection of surfactant type which is suitable for a specific oil field to increase the oil production should fulfill the selection criteria. Laboratory works firstly should be done to evaluate the important properties based on the industrial standard procedures. These laboratory tests include compatibility test, aqueous stability test, phase behavior study, micro-emulsion viscosity, interfacial tension determination, thermal stability test, and filtration test.